Barriers to optimal diabetes care in Trinidad and Tobago: a health care Professionals’ perspective - Roopnarinesingh, Nira; Brennan, Nancyellen; Khan, Claude; Ladenson, Paul W.; Hill-Briggs, Felicia; Kalyani, Rita Rastogi (BMC health services research, 2015)
Background The republic of Trinidad and Tobago (T&T) is a middle income country with a comparatively high prevalence of diabetes mellitus (DM) compared to others in the Caribbean. To date, there have been no studies on health care professionals’ (HCP) perspectives regarding the barriers to achieving optimal care of patients with DM in this country and few previous studies in the Caribbean, yet such perspectives are imperative to develop strategies that reduce the global burden of this disease. Methods An electronic invitation was sent to prospective HCP in T&T inviting them to attend a symposium on DM and cardiovascular disease. A total of 198 HCP participants attended of whom approximately 100 participants completed an Audience Response Survey at the completion of the conference. The Audience Response Survey included questions regarding access to resources, need for prevention and education, and coordination of care for to diabetes care in T&T. Responses were analyzed in aggregate. Results The 198 HCP participants attending the symposium included mostly nurses (40 %) and physicians (43 %). The most common specialty indicated by the 198 HCP participants was Internal and Family Medicine (28 %), followed by Anesthesiology (7 %), Emergency Medicine (6 %), Endocrinology and Diabetes (5 %) and Cardiology (3 %). Among the ~100 HCP who completed the Audience Response Survey, multiple barriers to achieving optimal care of patients with diabetes were reported such as: limited access to blood testing (75 %), ophthalmological evaluations (96 %), ECGs (69 %), and cardiac stress tests (92 %); inadequate time to screen and evaluate DM complications (95 %); poor access to consultants for referral of difficult cases (77 %); and lack of provider education regarding cardiovascular complications of DM (57 %). HCP agreed that nurses could potentially be considered to have a more active role in the care and prevention of cardiovascular disease and diabetes through leading patient education efforts (98 %), screening patients for complications (91 %), coordinating care efforts (99 %) and educating family members (98 %). Conclusions The HCP in our study reported significant barriers to achieving optimal diabetes care in T&T. In the future, such barriers to care will need to be addressed in order to respond to the projected growth of diabetes in developing countries both within the Caribbean and globally.